Tindak Pidana dalam Praktik Jurnalistik: Batas Kebebasan Pers dan Perlindungan Hukum - Fauqa Shafa Qurbani; Henny Yuningsih (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
Freedom of the press is one of the pillars of democracy guaranteed by the constitution and international law, but it is not absolute because it is still limited by legal norms to protect the public interest, individual reputation, and public order. This study aims to analyze criminal acts in journalistic practice by highlighting the limits of press freedom and forms of balanced legal protection. The method used is normative legal research with a statutory, conceptual, and case-based approach. The results of the study indicate that there is potential for criminalization of journalists due to the use of criminal articles in the Criminal Code and the ITE Law, which has a chilling effect on the work of the press. Therefore, the resolution of news disputes should prioritize the right of reply, the right of correction, and mediation mechanisms of the Press Council. Criminal sanctions should only be used as an ultimum remedium if there is proven malicious intent and serious harm. In conclusion, the protection of press freedom must be balanced with legal responsibility to create a free and accountable press system.